The essence and main factors of formation of an entrepreneurial climate - A. Z. Gusov; A. A. Baitursunov (Путеводитель предпринимателя)
This article is devoted to the formation and development of a favorable entrepreneurial climate. In the context of the issue under consideration, the structural characteristics of the entrepreneurial climate based on the Doing Business rating. The presented research has the task ofdetermining the basic factors that shape the entrepreneurial climate, in this case, in the context of individual countries.